Four new species of Arixyleborus Hopkins, 1915, ambrosia beetles from Thailand (Coleoptera: Curculionidae: Scolytinae: Xyleborini) - Sittichaya, Wisut; Beaver, Roger A.; Smith, Sarah M. (Zootaxa, 2024)
Four new species, Arixyleborus halabala Sittichaya, Beaver & Smith sp. nov., Arixyleborus longicauda Sittichaya, Beaver & Smith sp. nov., Arixyleborus vellus Sittichaya, Beaver & Smith sp. nov. are described from Thailand, and Arixyleborus liratus Sittichaya, Beaver & Smith sp. nov. from Thailand and East Malaysia (Sabah). With the inclusion of the species described here, the diversity of Arixyleborus is increased to 46 species, of which 20 occur in Thailand. A synoptic list with distributions and habitat types is provided.